PENGARUH KOMITMEN DAN MOTIVASI TERHADAP KINERJA PADA KARYAWAN KADIN DKI JAKARTA - FRANS NELLY. T T; HENRY ERYANTO (Jurnal Ilmiah Econosains, 2013)
ABSTRACTThe study aims to determine whether there is effect commitment and motivation to performance of the employee Kadin DKI Jakarta and also to get a valid and reliable data or fact, to prove it. The research has been done for three months since January until March 2013. The method of this research is survey. The population research was all employee of KADIN DKI Jakarta as much as 61 employees. And the sample used as many 51 employees by using simple random sampling. Data variabel Y (performance) is a secondary data obtained from performance appraisal January until February 2013. The result reveals that there is a possitive and significance effect between commitment to performance, and also motivation to performance, and then there is a possitive and significance effect between commitment and motivation to performance of employee KADIN DKI Jakarta.Keywords: commitment, motivation, performance